TRANSFORMING HIGHER EDUCATION THROUGH BILINGUAL PROJECT-BASED LEARNING - Evelyn Odonkor; Patricia W. Cummins; Emily Eichmann; Oualid Benalla (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Higher education is increasingly challenged to connect language learning with interdisciplinary, real-world applications. This paper examines two Collaborative Online International Learning (COIL) projects in which advanced French students in the United States collaborated with business English students in Côte d’Ivoire (2024), and with economics and entrepreneurship students in France and Morocco (2025). These projects integrated language learning with business, sustainable development goals, and social issues, aligning with the “Five Cs” framework of world languages: communication, culture, connections, comparisons, and communities. As an alternative to traditional study abroad, COIL functioned as a form of virtual mobility, expanding access to intercultural experiences across four institutions. The projects reflect a broader shift in U.S. world language curricula from literature-based instruction toward applied, interdisciplinary learning. Students engaged in shared assignments adapted to different disciplinary contexts, collaborating bilingually in English and French to address complex global challenges. Final projects were developed and presented in both languages, fostering linguistic proficiency alongside professional and intercultural competencies. Findings suggest that bilingual project-based COIL models can enhance language acquisition, support interdisciplinary collaboration, and better prepare students for globalized professional environments. This approach offers a scalable model for transforming higher education through inclusive, practice-oriented internationalization.